Plain proposal : a daughters of the promise novel - Wiseman, Beth, 1962- (2015)
Miriam secretly vows to follow Saul no matter what the future holds. She never thought that future might take them away from their Amish community.
Includes excerpt: Her brother's keeper.
Keywords: Amish -- Fiction; Man-woman relationships -- Fiction